Interactive Learning Resources for the Digital Age: A Needs Analysis of Digital Textbook Development: Sumber Belajar Interaktif untuk Era Digital: Analisis Kebutuhan Pengembangan Buku Ajar Digital - Ria Wulandari; Noly Shofiyah; Machful Indra Kurniawan; Rikhatul Jannah; Kofifah Silfanah (Universitas Muhammadiyah Sidoarjo, 2024)
The purpose of this research is to analyze the need for developing digital textbooks as interactive learning aids in the digital era. A survey with a research instrument in the form of a questionnaire was utilized as the research method. The questionnaire was distributed to 40 class VII pupils. Data analysis techniques employ descriptive statistics to identify the primary needs of students, as well as the design and desired interactive elements in digital textbooks. According to the requirements analysis, digital textbooks must have practice questions and answer keys, video and audio, student activity sheets, and relevant pictures. Furthermore, digital textbooks are simple to use, with Indonesian, colorful, easy-to-understand content and easy-to-read font kinds and sizes. These findings will serve as the foundation for the creation of digital textbooks that will improve the efficacy of learning in the digital age. Highlights : Interactive Elements: Digital textbooks should include practice questions, answer keys, multimedia (video and audio), activity sheets, and relevant images. User-Friendly Design: Textbooks need to be easy to use with clear, colorful content, and easy-to-read fonts in the Indonesian language. Educational Impact: The development of digital textbooks based on these findings aims to enhance the effectiveness of learning in the digital age. Keywords : digital era; digital textbook; interactive learning resources; needs analysisv